Cochlear Implantation in Children With Congenital Unilateral Deafness: A Case Series. Issue 10 (December 2017) - Beck, Rainer Linus; Aschendorff, Antje; Hassepaß, Frederike; Wesarg, Thomas; Kröger, Stefanie; Jakob, Till F.; Arndt, Susan
Abstract : Objectives: Cochlear implant is regarded as a treatment option for hearing rehabilitation of adults with unilateral sensorineural hearing loss. A clear benefit has been experienced in regard to speech comprehension in noise, localization, and quality of life. The aim of this study was to investigate the benefit of cochlear implantation for children with congenital unilateral hearing loss. Study Design: Retrospective case series. Setting: Tertiary referral center; cochlear implant program. Patients: Ten children with congenital unilateral hearing loss. Intervention: After extensive consultation with the families and intensive counseling, the children received a cochlear implant. Main Outcome Measures: Categories of auditory performance, speech discrimination in open set, subjective assessment by Speech, Spatial and Qualities scale questionnaire. Conclusion: Eight of ten children use their cochlear implant consistently on a daily basis. Two children who were equipped with an implanted device at a later age tend to nonuse of the device. The evaluation of binaural hearing in small children is still difficult and methods have to be developed to allow objective assessment.